The measurement of lower tear meniscus height using Anterior segment digital imaging and keratography - Rosmadi, Nurin Izzati; Yusoff, Nur Hanisah Diyana; Hilmi, Mohd Radzi; Mohd Kamal, Khairidzan; Ithnin, Mohd. Hafidz (Management Science University (MSU), 2019)
The difference of lower tear meniscus height (TMH) value between invasive and non-invasive techniques is under explained. This study aims to compare the value of lower TMH between Oculus keratograph 5M (OK5M) and anterior segment digital imaging (ASDI) using slit lamp with iPhone6 video recorder attached. The totals of twenty participants with 40 eyes were involved in this cross-sectional study. Right and left eyes from an individual were considered separately. Instillation of fluorescein sodium was applied on the ASDI technique only. Three measurements of TMH were taken from each methods and average were calculated and recorded. Independent sample t-test was used to analyze the data and it was found that the mean of the TMH measurement from the ASDI (0.42 ± 0.11 mm) was higher than the mean from the OK5M (0.25 ± 0.06 mm). The comparison between two methods was significant (p < 0.05). In conclusion, this study suggested that the higher TMH in ASDI was resulted by the effect of fluorescein and together with local climate.